Visualization of students’ cognitive knowledge in digital concept mapping - Gabriela Stefkova; Jana Michalkova; Lucia Dimunova; Beata Gress Halasz (International Journal of Evaluation and Research in Education (IJERE), 2024)
Meaningful learning through the creation a digital concept map is the easiest way to gain cognitive knowledge, new information, and possibility how to expand among learners. Only a few empirical studies have been conducted in the field of nursing regarding learning through concept mapping to achieve higher levels of knowledge and digital skills. The study evaluated the student’s ability to visualize cognitive knowledge by creating a digital concept map. The objectives were to identify the perception using digital technologies and conceptual mapping, differences and relationships between gender, age, years of study, and branches. We used the ContextMinds program map creation. There were 92 Slovak students of nursing, public health and physiotherapy participated in the study. Data were collected and analyzed using IBM SPSS version 25.0. Perception of learning using digital concept mapping strategy was assessed using descriptive statistics, where paired t-test, analysis of variance (ANOVA) and Chi-square were used. The study found a positive perception of creating the digital concept map, but a low level of digital skills. First-year students took one or more weeks to submit the final version of the concept map in comparison to third-year students who took one or more hours. For second-year students, a creation of a concept map was less problematic than for first-year students. Students prefer standard teaching and learning methods. Healthcare absolvents are required to be proficient in digital literacy. Applying cognitive knowledge to create a digital concept map is a challenging strategy procedure.